INFLUENCE OF STABILIZERS IN MELOXICAM NANOCRYSTAL FORMATION AND ITS APPLICATION ON SUSPENSION ORAL DOSAGE FORM - Magdalena Yuni Kristanti; Rachmat Mauludin; Heni Rachmawati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2013)
Meloxicam is a non steroid anti inflammatory drug that is classified as Biopharmaceutics Classification System (BCS) class II. Meloxicam is poorly soluble in water, therefore its solubility would be the rate limiting step for drug absorption. This study was conducted to improve meloxicam solubility using nanotechnology approach. Meloxicam nanocrystal was prepared using high pressure homogenization technique. Several stabilizers were investigated for suitable nanocrystal production. Formulation of suspension on the meloxicam nanocrystal was developed. Short physical stability was performed to assess the potential use of the stabilizer. Nanocrystal containing 10% meloxicam and 5% PVP K25 was formed faster with better physical stability compared to other stabilizers (xanthan gum, HPMC 2910 type 603 dan 645). Meloxicam nanocyrstal suspension containing meloxicam nanocrystal with stabilizer 5% or 10% of PVP K25 showed excellent particle size stability (with particle size 466.6nm and 486.9nm) and dissolution rate compared to reference product (without nanonization). Particle size and dissolution rate of meloxicam nanocrystal suspensions (containing 5% or 10% of PVP K25) were stable after storage for 30 days at room temperature. Kinetic solubility of meloxicam nanocrystal was three times higher than that of meloxicam. According to XRD profile, there was no differences in crystallinity between meloxicam and meloxicam nanocrystal.Key words: meloxicam, high pressure homogenizer, nanocrystal,dissolution rate, kinetic solubility